Investigation of the influence of plasma source power on the properties of magnetron sputtered Ta2O5 thin films - Bärtschi Manuel (EDP Sciences, 2021)
To enable the production of sophisticated optical interference coating designs, coatings with very low absorption and stray light losses and excellent layer thickness deposition accuracy are required. The selection and optimization of suitable coating materials and deposition processes are consequently essential. This study investigated the influence of the plasma source power on the optical properties, layer uniformity and stress, scattered light behavior and optical losses of magnetron sputtered Ta2O5 thin films.